Perspectives of Various Stakeholders Towards the Role of Speech Language Therapists in the Management of Infants with Swallowing and Feeding Difficulties: A Nationwide Survey in the State of Kuwait - Alquraini, Fatemah (Trinity College Dublin. School of Linguistic Speech & Comm Sci. Discipline of Clin Speech & Language Studies, 2022)
Background Dysphagia is commonly seen in preterm and low birth weight (LBW) infants and can heavily impact both the infant’s and caregiver’s quality of life. Speech Language Therapists (SLTs) have the duty and expertise to assess and treat infant’s feeding and swallowing skills, as well as guide parents on safe feeding together with a multidisciplinary team (MDT). In Kuwait, the prevalence of such cases is high and SLTs were only recently added to the neonatal intensive and special care units (NICU/SCBU), in addition to out-patient clinics for infant monitoring. To date, no studies have examined understanding of SLTs’ role in such settings. Aims The study was aimed at medical professionals and caregivers within the NICU/SCBU and out-patient clinics. The purpose was to 1) identify the level of awareness of SLTs’ profession, 2) establish an understanding of the practices done, 3) and acquire suggestions for designing and delivering a training program that teaches parents safe feeding methods. Included as well was recognizing the levels of knowledge and comfort in service provision, and the level of caregivers’ comfort in infant feeding. Methods Two anonymous web-based surveys (Qualtrics) were designed. Gatekeepers disseminate the surveys via convenience sampling to five hospitals located in four of six governorates. Descriptive and inferential data analysis were done using SPSS program, and content analysis for text-entry responses was applied. Results A total of 133 responses were from healthcare professionals and 21 from parents.’ Healthcare workers generally had higher levels of awareness of SLTs’ profession compared to caregivers. There was a strong association between levels of knowledge and comfort in the medical staff group. Most caregivers were somewhat comfortable on how their infant is fed. Shared themes between the two groups in terms of potentially creating a training program were to provide live and in-person demonstrations of feeding techniques and breastfeeding guidance, all within a short duration and group-based. Conclusion This study shows the targeted groups’ knowledge of SLTs’ discipline, present practices, and participants’ opinions on training program content and mode of delivery. These preliminary data aid in determining steps to raise the level of awareness of SLTs’ role in infant care and improve services via promoting MDT and increasing their clinical skillset.
Keywords: Perspectives; dysphagia; infants; NICU; Speech Language Therapist